La FORMALIZACIÓN DE EMPRENDEDORES Y SU RELACIÓN EN LA CONTRIBUCIÓN TRIBUTARIA A LA SUNAT EN LA PROVINCIA DE CORONEL PORTILLO - Ruiz de la Cruz, Jhonn Robert (2024)
Objective: Determine the relationship between the formalization of entrepreneurs and their tax contribution to SUNAT in the province of Coronel Portillo. Method: An applied research design with a quantitative, non-experimental, transversal and correlational approach was used. Data collection was carried out through surveys, using a questionnaire as an instrument. For the analysis, Spearman's statistical evaluation test was applied, obtaining a Rh0 coefficient of 0.893, which indicates a strong relationship between the variables. Results: The results showed that the entrepreneurs' intention to formalize is not necessarily linked to their level of tax culture. Some entrepreneurs with low tax knowledge express interest in formalizing, while others with greater tax culture did not do so due to distrust of the State. Conclusion: The formalization of entrepreneurs significantly influences their tax contribution, as indicated by the high correlation coefficient found. However, trust in the State is presented as a determining factor in the formalization process, showing that promoting tax culture alone does not guarantee an increase in tax contributions.